Is longer unemployment rewarded with longer job tenure? - Miki Kohara; Masaru Sasaki; Tomohiro Machikita (Institute for the Study of Labor (IZA), 2012)
This paper examines whether or not a prolonged unemployment period can raise the quality of job matching after unemployment. We focus on job tenure as an indicator of a good quality job match after unemployment. We match two sets of Japanese administrative data compiled by the public employment security offices: one includes information about the circumstances of job seekers receiving unemployment insurance, and the other includes information about job seekers applying for jobs. We first show a negative relationship between unemployment duration and the subsequent job duration. Restricting the sample to job seekers who changed search behaviors in the final 59 days before expiration of unemployment insurance, we secondly show an even greater negative effect of unemployment duration on the following job duration. The importance lies not only in the duration of unemployment. If job seekers keep a high reservation wage and a low search intensity because of the benefits of unemployment insurance, and change them in response to the expiration of insurance, prolonged unemployment will result in short job duration after unemployment.
Keywords: J64; J65; J68; 330; unemployment duration; unemployment insurance; job search; job stability; administrative data; Japan; Arbeitslosigkeit; Dauer; Arbeitsuche; Arbeitslosenversicherung; Arbeitsplatzsicherung; Betriebszugehörigkeit; Japan